2014
DOI: 10.1097/mib.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

Skin Reactions During Anti-TNFα Therapy for Pediatric Inflammatory Bowel Disease

Abstract: Skin reactions are common during maintenance therapy with infliximab in pediatric patients. For most patients, skin reactions seem to correlate with a low level of intestinal inflammation. Although potentially harsh, skin lesions mostly allow continuation of infliximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 30 publications
7
57
3
Order By: Relevance
“…Th ese diff erences could be explained by the systematic enquiry for cutaneous lesions and referral to a dermatologist in our center. In a prospective study on pediatric IBD patients, an attentive and double-checked clinical examination by nurses and physicians revealed a skin lesions rate of 47.6% ( 23 ). Psoriasis more frequently aff ected women (69.5%) and patients with CD (88.1%) in our study: these results are comparable with previous data reviewed by Torres et al ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Th ese diff erences could be explained by the systematic enquiry for cutaneous lesions and referral to a dermatologist in our center. In a prospective study on pediatric IBD patients, an attentive and double-checked clinical examination by nurses and physicians revealed a skin lesions rate of 47.6% ( 23 ). Psoriasis more frequently aff ected women (69.5%) and patients with CD (88.1%) in our study: these results are comparable with previous data reviewed by Torres et al ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…Th is cumulative incidence is similar to the one observed in another French retrospective study, which found a cumulative incidence of cutaneous events of 22% (207 patients on a total of 922) ( 22 ). A recent prospective study, carried on a pediatric population of IBD patients treated with IFX, found a higher incidence of cutaneous events in nearly 50% of patients, with 23.8% of them having severe lesions ( 23 ). Previous studies found that CD was signifi cantly associated with onset of cutaneous infections, which had never been demonstrated before.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similarly, anti-TNF agents, among the most effective treatments for psoriasis, occasionally cause psoriasis. [176][177][178][179] The particular hallmarks of anti-TNF induced psoriasis, more common in women than in men, is a distribution on palms, soles, and the scalp (fig 2). 180 A recent multicenter study of 7415 patients in Spain, treated for IBD with anti-TNF drugs, noted an incidence of psoriasis of 0.5% per patient year.…”
Section: Skin Lesionsmentioning
confidence: 99%